Effects of increasing lysine:calorie ratio and dietary fat addition on growth performance and carcass characteristics of growing-finishing gilts - M De La Llata; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
An experiment using 1,200 gilts (60 to 260 lb) was conducted to determine the effects of increasing lysine:calorie ratio and dietary fat addition on growth performance and carcass characteristics. Dietary treatments were arranged in a 2 x 4 factorial with two levels of dietary fat (0 and 6%) and four lysine:calorie ratios in each of the four phases. The appropriate lysine:calorie ratios to maximize growth performance were: 3.56, 2.50 to 2.75, 2.04, and 1.72 from 60 to 100 lb, 100 to 165 lb, 165 to 220 lb, and 220 to 260 lb, respectively. These ratios equate to approximate total lysine levels of 1.15, .90, .75, and .58%, respectively, in corn-soybean meal-based diets with no added fat.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Lysine:calorie ratio; Fat; Lysine; Finishing pigs